Genome-Wide DNA from Degraded Petrous Bones and the Assessment of Sex and Probable Geographic Origins of Forensic Cases - Gaudio, Daniel (2019)
The acquisition of biological information and assessment of the most probable geographic origin of unidentified individuals for obtaining positive identification is central in forensic sciences. Identification based on forensic DNA, however, varies greatly in relation to degradation of DNA. Our primary aim is to assess the applicability of a petrous bone sampling method in combination with Next Generation Sequencing to evaluate the quality and quantity of DNA in taphonomically degraded petrous bones from forensic and cemetery cases. A related aim is to analyse the genomic data to obtain the molecular sex of each individual, and their most probable geographic origin. Six of seven subjects were previously identified and used for comparison with the results. To analyse their probable geographic origin, samples were genotyped for the 627.719 SNP positions. Results show that the inner ear cochlear region of the petrous bone provides good percentages of endogenous DNA (14.61-66.89%), even in the case of burnt bodies. All comparisons between forensic records and genetic results agree (sex) and are compatible (geographic origin). The application of the proposed methodology may be a powerful tool for use in forensic scenarios, ranging from missing persons to unidentified migrants who perish when crossing borders.